2020
DOI: 10.1016/j.cortex.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of phonological information to visual word recognition: Evidence from Chinese phonetic radicals

Abstract: Lateralization is a critical characteristic of language production and also plays a role in visual word recognition. However, the neural mechanisms underlying the interactions between visual input and spoken word representations are still unclear. We investigated the contribution of sub-lexical phonological information in visual word processing by exploiting the fact that Chinese characters can contain phonetic radicals in either the left or right half of the character. FMRI data were collected while 39 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This pattern might due to the relatively lower spatial resolution of ERP measures. Recent Chinese neuroimaging studies demonstrated that phonological processing involved multiple brain areas 45 47 , such as left inferior parietal lobule and right superior temporal gyrus. Moreover, a meta-analysis with eight fMRI studies revealed a bilateral involvement of the ventral occipito-temporal regions for both phonological and semantic processing 46 .…”
Section: Discussionmentioning
confidence: 99%
“…This pattern might due to the relatively lower spatial resolution of ERP measures. Recent Chinese neuroimaging studies demonstrated that phonological processing involved multiple brain areas 45 47 , such as left inferior parietal lobule and right superior temporal gyrus. Moreover, a meta-analysis with eight fMRI studies revealed a bilateral involvement of the ventral occipito-temporal regions for both phonological and semantic processing 46 .…”
Section: Discussionmentioning
confidence: 99%
“…They consisted of 4–17 strokes (mean = 8.62, SD = 3.02), and their mean frequency was 20.12 per million (SD = 56.60). All materials had left–right configuration with the phonetic radicals situated in the right half of the character to eliminate the confounding effects of phonetic radical position (Liu et al, 2020 , 2022 ). The characters formed 561 pairs (34 × [34–1]/2 = 561) in the following four categories in terms of orthographic and phonological similarities: (1) 28 pairs that were similar in orthography and phonology; (2) 33 pairs that were similar in orthography but different in phonology; (3) 52 pairs that were different in orthography but similar in phonology; and (4) 448 pairs that were different in orthography and phonology.…”
Section: Methodsmentioning
confidence: 99%
“…117-118); indeed, "nobody is disputing the role that phonological components play in the Chinese writing system or the role that phonological recoding plays in the reading of Chinese" (Handel, 2015, p. 130 see also Coulmas, 1996a;Sampson, 1985Sampson, , 2017Unger & DeFrancis, 1995). Nor is this phonetic information inert: There is massive psychological and neuropsychological evidence that Chinese readers process writing using phonological cues (Dehaene, 2010;Li, Peng, Liu, Booth, & Ding, 2014;Liu, Vermeylen, Wisniewski, & Brysbaert, 2020).…”
Section: What Glottography Meansmentioning
confidence: 99%